Pembuatan Modul Gambar Teknik Listrik Berbasis Autocad di Sekolah Menengah Kejuruan - M. Ronald Azura; Hambali Hambali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
Electrical Engineering Drawing is one of the compulsory subjects that must be studied for students. In the implementation of learning at SMK N 2 Kota Sungai Kunci this subject is still done manually, namely by using pencils and drawing paper. However, with the empowerment of computer labor, it can carry out the learning process of Electrical Engineering Drawings with the help of Autocad software. Therefore, it is necessary to make an Electrical Engineering Drawing learning module to support students in understanding the use of software in understanding material. This study aims to determine the validity and feasibility of the Autocad-based Electrical Engineering Drawing module at SMK N 2 Kota Sungai Lilin. Based on the results of the research that has been done, data is obtained from a questionnaire analysis by a validator consisting of 2 material experts and media experts. The results of the validity test of the Autocad-based Electrical Engineering Drawing learning module assessed by the material expert validator obtained a very high validity category while the media expert validator obtained a very high validity category. The results of the due diligence conducted by 34 class X students of the Department of Electrical Power Installation Engineering obtained a very decent category. So, the conclusion from this study is that the Autocad-Based Electrical Engineering Drawing module is feasible to be used in the learning process of Electrical Engineering Drawings for class X of the Electrical Engineering Department.